Tri Hita Karana Values in Magebagan Tradition - Adiwijaya, Pande Agus; Sutajaya, I Made; Suja, I Wayan; Numertayasa, I Wayan; Wedayanthi, Luh Made Dwi (Badan Riset dan Inovasi Daerah Provinsi Bali, 2024)
Purpose: This research is aimed at describing the values contained in the magebagan tradition in Bali in terms of the Tri Hita Karana philosophy. Design/methodology/approach: This research uses a qualitative approach which is explained descriptively. Research data was collected through observation, interviews and literature review. Data were analyzed and described qualitatively Findings: It was found that in the parhyangan aspect the value contained is respect and devotion to ancestors which is vertically the same as the relationship between humans and God through ancestors. In the pawongan aspect, the magebagan tradition is very full of meaning of solidarity, solidity and mutual cooperation. From the palemahan aspect, through the magebagan tradition, safe and comfortable conditions will be created for the bereaved family spiritually and materialistically. Implications: The magebagan tradition is not free from negative stereotypes but this tradition is also full of meaning. Negative practices that can reduce the meaning of this tradition need to be reduced so that later this tradition can remain the color of the noble Balinese culture.